Vertigo : five physician scientists and the quest for a cure - Baloh, Robert W. (Robert William), 1942- (Oxford University Press, 2017)
Vertigo: Five Physician Scientists and the Quest for a Cure follows this centuries long trek. The book follows the key discoveries made by Prosper Meniere (1799-1862) who first recognized that vertigo could originate from the inner ear, Josef Breuer (1842-1925) who conducted groundbreaking research on the inner ear during his evenings at home after he spent his days working in a busy private medical practice, Robert Barany (1876-1936) who received the Nobel Prize for his early work on the inner ear, Charles Hallpike (1900-1979) who showed that BPPV originates from the inner ear, and Harold Sch.